PENERAPAN ALGORITMA RC4 PADA OPERASI XOR UNTUK KEAMANAN PESAN PADA SMARTPHONE BERBASIS WEB - Awaludin, Muryan (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2017)
Utilization of cryptography as the encryption and decryption can be used to secure messages or the data that is important and valuable. A message can be encrypted or into ciphertext using a key and can be safely exchanged without having to worry about the confidentiality of the contents of the message. Decryption key will be to process the encrypted message into plaintext or the original message. XOR operation algorithm is computationally easy to use, but the process XOR algorithm is weak and not strong. To cover up weaknesses reviews these use RC4 algorithm (Rivers Code 4), because RC4 algorithm process is fast and strong . The results of this application in the form of a software is Able to encrypt and decrypt the message form and to generate a unique security key based encrypted message, and provide an accurate report on the presence or absence of changes to the contents of the message, The implementation of the RC4 encryption and decryption process on the website based smartphone helps users in maintaining the security and confidentiality of information storage that is sent and received. The results of this study so that the user can secure messages to be sent to the recipient.